Enhancing Consumer Brand Engagement in Social Media Marketing for Wedding Organizer Services - Salsabela, Riska Nadiya; Widadi, Budi (ITB AAS Indonesia Surakarta, 2024)
This study aims to examine the impact of Value Co-Creation on Consumer Brand Engagement within the context of social media marketing for wedding organizer (WO) services. The sample was selected using purposive sampling, with a total of 120 respondents who are WO service users and active on social media. The data analysis technique employed is Structural Equation Modeling (SEM) using the AMOS software, and data was collected through a questionnaire. The findings reveal that five hypotheses have a positive and significant influence: entertainment on value co-creation, interactivity on value co-creation, EWOM on value co-creation, trendiness on value co-creation, and value co-creation on consumer brand engagement . However, one hypothesis, concerning customization's effect on value co-creation, was found to be insignificant.